2021
DOI: 10.1186/s40246-021-00349-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-TUG1 promotes the progression of infantile hemangioma by regulating miR-137/IGFBP5 axis

Abstract: Background Previous studies indicated that lncRNA taurine upregulated gene 1 (TUG1) played essential roles in human cancers. This study aimed to investigate its function in infantile hemangioma (IH). Methods A total of 30 pairs of clinical infantile specimens were used in this study. The expression of TUG1 in IH tissues was assessed by quantitative reverse transcriptase PCR (qRT-PCR). Two short hairpin RNA targeting TUG1 (sh-TUG1-1 and sh-TUG1-2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Migration and invasion of transfection HEMECs were detected by Transwell assay. The specific experimental procedures refer to the research of Zhou et al [ 23 ]. All samples were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Migration and invasion of transfection HEMECs were detected by Transwell assay. The specific experimental procedures refer to the research of Zhou et al [ 23 ]. All samples were run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA-TUG1 promotes the proliferation, migration, and invasion of HemECs by regulating the miR-137/IGFBP5 axis. 28 Silencing MALAT1 significantly inhibits the proliferation, migration, and angiogenesis of HemECs, but promotes apoptosis. 29 MIR4435- 2HG participates in the progression of several human diseases and interacts with DNA, RNA, or proteins to regulate transcription, epigenetic modifications, protein/RNA stability, translation, and post-translational modifications.…”
Section: Discussionmentioning
confidence: 97%
“…Studies demonstrated that IGFBP5 overexpression abrogated the miR-204-5p induced decrease in cell viability and colony formation, and reversed miR-204-5p induced apoptosis, indicating that miR-204-5p could be acting as a tumor suppressor through its downregulation of IGFBP5 ( 94 ). In infantile hemangioma, miR-137 was found to regulate IGFBP5 expression, and this signaling axis is under the control of the long-noncoding RNA taurine upregulated gene 1 (TUG1) ( 104 ). TUG1 knockdown resulted in increased miR-137, which decreased expression of IGFBP5, and inhibited tumorigenesis in vivo , indicating that TUG1 acts in an oncogenic manner potentially through the upregulation of IGFBP5 ( 104 ).…”
Section: Oncogenic Activity Of Igfbp5mentioning
confidence: 99%
“…In infantile hemangioma, miR-137 was found to regulate IGFBP5 expression, and this signaling axis is under the control of the long-noncoding RNA taurine upregulated gene 1 (TUG1) ( 104 ). TUG1 knockdown resulted in increased miR-137, which decreased expression of IGFBP5, and inhibited tumorigenesis in vivo , indicating that TUG1 acts in an oncogenic manner potentially through the upregulation of IGFBP5 ( 104 ).…”
Section: Oncogenic Activity Of Igfbp5mentioning
confidence: 99%